Virtual reality authoring tools acceptance and use: An exploratory study with the UTAUT2 model - de Oliveira, Vinícius Pires; Macedo, Rodrigo de Jesus; de Freitas, Fabio Vinicius; Machado, Andrea; Murari, Thiago; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Virtual reality holds significant potential for optimizing production processes, reducing costs, and contributing to the achievement of sustainable development goals outlined by the United Nations. As such, this study aims to understand the technological acceptance and use of virtual reality authoring tools. The study followed the Design Science Research paradigm, in which four virtual reality authoring tools, namely NVIDIA Omniverse Create, Spatial, SimLab Composer and SimLab VR Viewer, were filtered based on criteria established in literature, then participants experimented the non-immersive SimLab Composer and the immersive SimLab VR Viewer in Quest 2 headsets, with their perceptions on acceptance and use collected with the UTAUT2 model. Through the experiment, the immersive authoring tool were perceived as easy to acquire and develop skills with, competitively priced, and capable of providing a fun user experience. However, difficulty arise when establishing a correlation between real-world physical movements and the expected actions within the immersive environment. This discrepancy may have contributed to the participants below than positive assessment of the knowledge required to effectively utilize the tools. Nonetheless, they expressed their intention to use the VR authoring tools in the future, although without a commitment to regular usage. This study serves as a valuable indicator and provides a foundation for future investigations for evaluating authoring tools in virtual reality.